Students’ satisfaction towards Internship program: a study among Bachelor Degree Students, Faculty of Hotel and Tourism Management UiTM Terengganu / Nooreen Jazlina Jamaludin & Nur Ainina Amani Mohd Zaki - Jamaludin, Nooreen Jazlina; Mohd Zaki, Nur Ainina Amani (2018)
This undergraduate project is about students’ satisfaction toward the internship program. By achieving the level of student satisfaction is one of the achievement for fulfill the objective of internship program. If the programs are failed, it will affect the reputation of the program itself and at the same times will affect the performance of the student. This study are used a quantitative method and the survey are made via online survey. A total of 103 respondents were selected for questioning via stratified random sampling technique. The questionnaire are evaluated the students' satisfaction in terms of work experience, motivator and overall satisfaction. A 5-point Likert scale has been used in all questionnaire items. At the end of the result, its show that the majority of the respondents are satisfied with their internship.